Sosialisasi Implementasi Kurikulum Merdeka Belajar pada Tingkat Sekolah Dasar di Kota Ambon - Palinussa, Anderson L. (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aimed to socialize the implementation of the Merdeka Belajar (Freedom to Learn) Curriculum at the elementary school level in Ambon City. The Merdeka Belajar Curriculum emphasizes student-centered learning, differentiated instruction, and the strengthening of the Pancasila Student Profile. The activity was conducted on August 6, 2024, at the Elementary School Hall, involving teachers, principals, and school supervisors. The methods included material presentations, interactive discussions, and simulations of contextual project-based lesson plan development. The results indicated participants' enthusiasm and active engagement in understanding the philosophy of the new curriculum. Discussions revealed challenges such as limited understanding and resources. However, simulations demonstrated teachers' potential in designing locally contextual learning. This activity successfully enhanced teachers' comprehension, confidence, and commitment to implementing the Merdeka Belajar Curriculum. It is recommended that follow-up training and intensive mentoring be provided to support the continuous implementation of this curriculum.